Deduction Based Verification of Business Models - Klimek, Radosław; Skrzyński, Paweł; Turek, Michał (Weryfikacja modeli biznesowych metodą dedukcyjną, 2010)
The paper presents a formal verification of the business processes expressed in BPMN. Verification is based on deductive reasoning. Automatic transformations of basic BPMN workflow patterns to temporal logic formulae are introduced. These formulae constitute a system specification and they are later processed using semantic tableaux method. In general, such reasoning technique has many advantages over the traditional approach, i.e., the resolution method. The paper provides automatic transformations for five basic BPMN workflow patterns and the example process is provided with description in BPMN diagram. The related temporal logic formula is obtained through automatic transformations, then the algorithm of reasoning using semantic tableaux methodology is applied to verify the business model.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 147, s. 173-188
Keywords: deductive reasoning; business processes; BPMN; workflow design patterns; formal verification; semantic tablea